Need of Treatment Modification During Entecavir Therapy in Patients with Chronic Hepatitis B: Long-Term Follow-Up Results for 120 Months - Hae Rim Kim; Seong Hee Kang; Hyung Joon Yim; Sang Jun Suh; Young Kul Jung; Ji Hoon Kim; Yeon Seok Seo; Jong Eun Yeon; Kwan Soo Byun (Microorganisms)
Entecavir (ETV) may have limited antiviral efficacy in chronic hepatitis B (CHB) patients with a high baseline viral load, especially in cases of partial virologic response (PVR). This study evaluated the outcomes of prolonged ETV monotherapy, given the lack of clear evidence favoring continuation or combination therapy in such scenarios. We included 188 treatment-naïve patients on ETV 0.5 mg and compared antiviral responses between high viral load (HVL, ≥7 log10 IU/mL) and non-HVL groups for over up to 120 months in this study. Compared to the non-HVL group, the HVL group exhibited a lower cumulative virologic response (VR, <20 IU/mL) during the 10-year therapy period (p < 0.01). Antiviral resistance to entecavir (rtS202G + rtM204V + rtL180M) developed in three out of 90 patients in the HVL group. Patients with complete response at 6 months had a 100% likelihood of achieving VR, while 83.9% of patients with PVR at 6 months achieved VR by month 120 (p < 0.01). Multivariate analysis revealed that baseline HVL was a significant predictor of long-term VR at 120 months. In conclusion, CHB patients with baseline HVL and PVR at 6 months are prone to ETV resistance and inadequate response, warranting a modification in treatment strategy.